2020
DOI: 10.1074/jbc.rev120.009132
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational regulation of the major drug transporters in the families of organic anion transporters and organic anion–transporting polypeptides

Abstract: The Organic Anion Transporters (OATs) and Organic Anion Transporting Polypeptides (OATPs) belong to the solute carrier (SLC) transporter superfamily and play important roles in handling various endogenous and exogenous compounds of anionic charge. The OATs and OATPs are often implicated in drug therapy by impacting the pharmacokinetics of clinically important drugs and thereby, drug exposure in the target organs or cells. Various mechanisms (e.g., genetic, environmental, and disease-related factors, drug-drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 152 publications
1
16
0
Order By: Relevance
“…4b and c), however interestingly, removal of iron by DFO also led to a decrease (p = 0.032, one sample t test) in VIT-HA levels despite no change in RNA levels. As well as regulation at the mRNA and protein level, the function of transporters can also be regulated by changes in localisation (Lee et al, 2020).…”
Section: Vit Expression Is Regulated By Iron Availabilitymentioning
confidence: 99%
“…4b and c), however interestingly, removal of iron by DFO also led to a decrease (p = 0.032, one sample t test) in VIT-HA levels despite no change in RNA levels. As well as regulation at the mRNA and protein level, the function of transporters can also be regulated by changes in localisation (Lee et al, 2020).…”
Section: Vit Expression Is Regulated By Iron Availabilitymentioning
confidence: 99%
“…The expression, localisation and activity of transporters are frequently regulated by the availability of the substrate. This has been well established in model organisms (Conte and Walker, 2011;Gao and Dubos, 2021;Lee et al, 2020;Sorribes-Dauden et al, 2020) and was recently reported for the arginine transporter ApiAT1 in T. gondii (Rajendran et al, 2021). To determine if iron affects expression of VIT we performed qRT-PCR on the vit gene.…”
Section: Vit Expression Is Regulated By Iron Availabilitymentioning
confidence: 89%
“…4B and C), however interestingly, removal of iron by DFO also led to a decrease (p = 0.032, one sample t test) in VIT-HA levels despite no change in RNA levels. As well as regulation at the mRNA and protein level, the function of transporters can also be regulated by changes in localisation (Lee et al, 2020). We assessed the localisation of VIT-HA upon changes in iron levels.…”
Section: Vit Expression Is Regulated By Iron Availabilitymentioning
confidence: 99%
“…The Oat1 siRNA knockdown study showed a marked increase in the uptake of paeonol only in the MT cell line, whereas no significant change in the transport was observed in the WT cell line. Previous studies have shown several reasons for the variations in Oats and organic anion transporting polypeptides (OATPs), including post-translational modifications, cellular trafficking, and other degradation mechanisms [ 62 ]. Therefore, we hypothesized that there might be some alteration or mutation in the diseased MT cell line that results in the elevated uptake of [ 3 H]paeonol.…”
Section: Discussionmentioning
confidence: 99%